2020
DOI: 10.1523/eneuro.0273-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field ApplicationIn VivoRegulates Neural Precursor Cell Behavior in the Adult Mammalian Forebrain

Abstract: Deep brain stimulation (DBS), which uses electrical stimulation, is a well-established neurosurgical technique used to treat neurologic disorders. Despite its broad therapeutic use, the effects of electrical stimulation on brain cells is not fully understood. Here, we examine the effects of electrical stimulation on neural stem and progenitor cells (collectively neural precursor cells; NPCs) from the subventricular zone in the adult forebrain of C57BL/6J mice. Previous work has demonstrated that adult-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 63 publications
(104 reference statements)
3
32
0
Order By: Relevance
“…These NPCs are highly responsive to EF application, expanding in number through proliferation and enhanced cell survival, as well as differentiating into newborn neurons. 19 Most striking, NPCs are activated to migrate in a rapid and directed manner in the presence of an applied EF using well-established in vitro assays and live cell imaging. 15 Together, these NPC behaviors provide promise for the design and implementation of regenerative medicine strategies that aim to replace lost or damaged cells following injury or disease, yet several important questions remain unanswered that are pivotal to understanding how to optimize the NPC response.…”
Section: What Influences Galvanotaxis? Nature Versus Nurturementioning
confidence: 99%
See 3 more Smart Citations
“…These NPCs are highly responsive to EF application, expanding in number through proliferation and enhanced cell survival, as well as differentiating into newborn neurons. 19 Most striking, NPCs are activated to migrate in a rapid and directed manner in the presence of an applied EF using well-established in vitro assays and live cell imaging. 15 Together, these NPC behaviors provide promise for the design and implementation of regenerative medicine strategies that aim to replace lost or damaged cells following injury or disease, yet several important questions remain unanswered that are pivotal to understanding how to optimize the NPC response.…”
Section: What Influences Galvanotaxis? Nature Versus Nurturementioning
confidence: 99%
“…However, promising recent work has demonstrated that biphasic in vivo stimulation can enhance NPC migration and regulate cell behavior. 17 , 19 Transferring the in vitro parameters to in vivo settings will be a challenge as the microenvironment also has profound effects on galvanotaxis. The microenvironment plays an important role in what the cell perceives and as such, the galvanotactic response is highly sensitive, yet malleable, with the outcome dependent on the EF parameters such as strength and frequency and the cell's environment (e.g., extracellular matrix [ECM] and nearest neighbors, discussed next).…”
Section: What Influences Galvanotaxis? Nature Versus Nurturementioning
confidence: 99%
See 2 more Smart Citations
“…Together with molecular cues and physical factors, electrical currents appear to be another component of cell guidance. Several studies have shown that the application of an electric field increases neurogenesis (Stone et al, 2011 ; Sefton et al, 2020 ) and drives neuroblasts toward the cathode in cell cultures, SVZ explants, and acute brain slices (Babona-Pilipos et al, 2011 ; Cao et al, 2013 ). Human neuronal progenitor cells (hNPCs) also migrate to the cathode in response to an electric field (Feng et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%